A comprehensive study on physicochemical properties, bioactive compounds, and emulsified lipid digestion characteristics of Idesia polycarpa var. Vestita Diels fruits oil. (15th March 2023) - Xiang, Xuwen; Wen, Leyan; Wang, Zhirong; Yang, Gang; Mao, Jianmei; An, Xiaofeng; Kan, Jianquan
Graphical abstract: Highlights: Physicochemical, nutritional, and digestive properties of IPO were studied. IPO was rich in polyunsaturated fatty acids, particularly linoleic acid. IPO exhibited high levels of β-sitosterol, β-tocopherol, and α-tocopherol. IPO emulsion was digested more faster than OO during intestinal digestion. Triacylglycerols of IPO were more digestible with the highest extent of lipolysis. Abstract: Idesia polycarpa var. vestita Diels fruits oil (IPO) has the potential to broaden the availability of healthy vegetable oil and relieve pressure on the edible oil supply. In this study, we compared the physicochemical, bioactivity, and digestive properties of IPO, olive oil (OO), and soybean oil (SO) to comprehensively evaluate the edible potential of IPO. The results revealed no significant differences in relative density or refractive index among the three oils. IPO was rich in β-sitosterol (366.74 mg/100 g), β-tocopherol (8.42 mg/100 g), and α-tocopherol (37.10 mg/100 g). The digestive properties of IPO emulsion were investigated for the first time using in vitro simulated digestion. The IPO emulsion stood out regarding its free fatty acid release (88.03 %). Finally, the IPO emulsion released mainly unsaturated fatty acids and had a higher monoacylglycerol content. This study provides new insights into IPO as a high-quality edible vegetable oil.